Penguatan Toleransi Beragama Melalui Implementasi Nilai Sila Pertama Pancasila Di Sekolah Dasar - Yosefo Gule; Johannes Keliat; Eti Muliani; Evan Hartanta Barus; Pema Julianto Pandia; Desti Natalia Sembiring; Desli Mianda Maria Manik (LPPI UMN AL WASHLIYAH, 2025)
Strengthening religious tolerance through the implementation of the values of the First Principle of Pancasila—Belief in One Almighty God—is essential in shaping children’s character from an early age. This community service program was conducted at SD Negeri 040459 Berastagi with the aim of enhancing students’ understanding of the meaning of divine belief and its application in developing mutual respect among different religions. The methods employed included interactive socialization, educational games, illustrated storytelling, and value reflection activities. The results revealed a significant improvement in students’ comprehension of tolerance values and their demonstration of respectful behavior in school life. Teachers also gained new insights into integrating divine values into character education. This program highlights that the contextual implementation of the First Principle of Pancasila effectively strengthens tolerance and fosters a peaceful, harmonious, and civilized learning environment.